Answer:
x = 36°
y = 66°
z = 78°
Explanation:
General outline:
- Setup equations for each sentence
- Solve the resulting system
Setup equations:
Allowing the first angle to be x, the second to be y, and the third to be z, the three sentences describing the relationships between angle measures are given below:
- Eq1: x + y + z = 180°
- Eq2: y + z = 4x
- Eq3: z = y + 12°
Solve the system
Substituting equation 3, into equations 1 and 2
Eq1: x + y + z = 180°
x + y + (y+12°) = 180°
x + 2y + 12° = 180°
x + 2y = 168°
x = 168° - 2y
Eq2: y + z = 4x
substituting the result from equation 1, and Equation 3...
y + (y+12°) = 4*(168° - 2y)
2y + 12° = 672° - 8y
10y = 660°
y = 66°
Substituting back into Equation 3...
Eq3: z = y + 12°
z = (66°) + 12°
z = 78°
Substituting both y, and z into Equation 1...
x + y + z = 180°
x + (66°) + (78°) = 180°
x + 144° = 180°
x = 36°
So, the three angle measures are:
x = 36°
y = 66°
z = 78°
Verification
"The sum of the measures of the angles of a triangle is 180."
x + y + z = 180°
36° + 66° + 78° = 180°
True
"The sum of the measures of the second and third angles is four times the measure of the first angle"
y + z = 4x
66° + 78° = 4*(36°)
144° = 144°
True
"The third angle is 12 more than the second"
z = y + 12°
78° = 66° + 12°
True